Violation of Dapek Salah Customary Law in Bengkulu: Forensic Psychological Analysis Toward The Criminal Behavior of Indigenous - Rangga Jayanuarto1 , Khudzaifah Dimyati2, Absori Absori2, Natangsa Surbakti2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Every law is a system which means law bases on the unity of the mind. Customary law is understood as a law that lives in a “living law” society, legal values and a sense of justice that lives in society. All takes place after the values lived by the society under the filter of legal ideals and moral ideals prevailing in the society concerned. Without the law as an effective social control, humans potentially can lead to behavior that can bring destruction to humans. In Bengkulu, the law that lives in the community is known as the law of adat dapek salah. Violation of the law can be acts of a person or group of people who disturb the balance in the indigenous peoples. The violation of the law is an act of deviant behavior that is negative in which each culprit will be charged with various kinds of traditional sanctions. The research of forensic psychology analysis is needed to see the behavior of customary criminal crime in violation of customary law. The assessment is carried out to provide an overview of the mental state of the offender. This is in line with forensic psychology as the study of subjects in terms of cognitive, effective and behavior in relation to the legal process. Material and Method: This research is a qualitative research which produces descriptive data in the form of written or oral words from people and observed behavior. Qualitative research is also called naturalistic research. This study departs from naturalistic inquiry whose findings are not found from statistical calculations. Findings: Customary law of Dapek Salah in Bengkulu as a social model directs to accommodate the entire social system which includes the function of norm system. The function of norm system is to correct behavior that deviates from the relevant rules (violations). These rules are the framework of human behavior orientation (members of the social system). Norms are also often referred to as rules of conduct and blueprints for behavior in a society. This can also lead to anti-social behavior or asocial behavior which could be a factor causing criminal behavior. Criminal behavior toward the Dapek Salah law is an act that causes adverse reactions and corrections and the balance of the community. In the study of forensic psychology analysis, criminal behavior on the law depends on the perception of the respective actors. Aspects of perception consist of cognitive aspects (thoughts), affective aspects (feelings), and aspects of conation (behavior). Individual perceptions can influence and motivate subsequent behavior, if the object of perception is judged unpleasant then the behavior is negative. Conclusion: Violation of the Dapek Salah is a phenomenon, a person or group of people who violate customary law (criminal behavior) so as disturbing the balance in indigenous peoples’ value. In the forensic psychological analysis, criminal behavior of the law depends on the perception of the respective actors. Aspects of perception consist of cognitive aspects (thoughts), affective aspects (feelings), and aspects of conation (behavior). Individual perceptions can influence and motivate subsequent behavior, if the object of perception is judged unpleasant then the behavior is negative. In the basic concept of psychology, there is something wrong with the minds of the perpetrators so that they are involved in criminal behavior. Imbalance relationship between Id, Ego and Superego makes humans weak and consequently more likely to commit deviant behavior or criminal behavior.